The Relationship between Gastric Mucosa Mucous Thickness and Gastroscopic Findings in Patients Receiving Non-Steroidal Anti-Inflammatory Drugs - Dono Antono; Chudahman Manan; Harry Isbagio; Vera D. Joewono (The Indonesian Society for Digestive Endoscopy, 2002)
Non-steroid anti-inflammatory drugs (NSAID) can cause gastropathy and gastric mucosa, especially the mucous may play an important prevention role. This cross-sectional, single group study was conducted to know the difference in mucous thickness in antrum or corpus mucosa and the correlation of gastric mucous thickness to gastropathy. Patients who received NSAID from the rheumatology clinic were studied. Healthy subjects of 14 – 65 years old who never received NSAID were included as normal controls. Piroxicam 20 mg daily was given to the patients for 7 days, then gastroscopy and gastric mucosa biopsy with frozen section were performed. Specimens were stained with haematoxyline eosin and thickness of the mucous layer was measured using ocular micrometer. Thirty-two out of 70 patients participated in the study. All cases had hyperemia on gastroscopy with erosions and ulcer in 32 and 9 cases, respectively. The mean thickness of mucosa in distal antrum, proximal antrum and corpus was 28.5 ± 9, 37.4 ± 13.1 and 43.3 ± 13.1 microns, respectively. There was significant relationship between gastric mucosa mucous thickness with gastroscopic findings. In conclusion, this study confirmed that thickness of gastric mucosa mucous has an important role in preventing NSAID gastropathy and dyspeptic complaints in this kind of patients does not suggest abnormalities of gastric mucosa. Key Words: Gastric mucosa mucous thickness, NSAID, gastroscopy